Preclinical modeling of lower-grade gliomas - Tang, Lilly W.; Mallela, Arka N.; Deng, Hansen; Richardson, Timothy E.; Hervey-Jumper, Shawn L.; McBrayer, Samuel K.; Abdullah, Kalil G. (Frontiers in Oncology, 2023)
Models for human gliomas prove critical not only to advancing our understanding of glioma biology, but also to facilitate development of therapeutic modalities. Specifically, creating lower-grade glioma (LGG) models has been challenging, contributing to few investigations and the minimal of progress in standard treatment over the past decade. In order to reliably predict and validate the efficacies of novel treatments, however, LGG models need to adhere to specific standards that recapitulate tumor genetic aberrations and micro-environment. This underscores the need to revisit existing models of LGG and explore prospective models that may allow us to bridge the gap between preclinical insights and clinical translation. This review first outlines a set of criterions aimed to address the current challenges hindering model development. We then evaluate the strengths and weaknesses of existing preclinical models of LGG with respect to these established standards. The review concludes with discussing the potential future directions for integrating these models to maximize the exploration of disease mechanisms and therapeutics development.